Johan P. Olsen og B. Guy Peters (eds.), Lessons from Experience. Experiental Learning in Administrative Reforms in Eight Democracies, Oslo: Scandinavian University Press, 1996, 341 s,.NOK. 298,00. - Grønnegård Christensen, Jørgen (Politica, 1997)
-